2018
DOI: 10.1088/1741-2552/aaa039
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cuffing of cervical vagus nerve inhibits efferent fiber integrity in rat model

Abstract: We hypothesize that due to these unforeseen and unexplored physiological consequences of the chronically cuffed vagus nerve in a rat, that inflammatory modulation and other vagal effects by VNS may become unreliable in chronic studies. Given our findings, we submit that it would benefit the VNS community to re-examine methods used in previous literature to verify the efficacy of the rat model for chronic VNS studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 72 publications
3
33
0
Order By: Relevance
“…Vagus nerve recordings have been conducted under anesthesia for both acute (WOODBURY & WOODBURY 1991;Caravaca et al 2017;Dias Da Silva et al 2002;Krolczyk et al 2008) and chronic models (Caravaca et al 2017;Sauter et al 1983). Others have chronically recorded from the peripheral sciatic nerve in awake rat models (Michoud et al 2017;Srinivasan et al 2015;Gore et al 2015;Srinivasan et al 2016;Musick et al 2015;Vasudevan et al 2017) and from the vagus nerve in anesthetized rat models (Khodaparast et al 2014;Khodaparast et al 2016;Somann et al 2018), but these devices have not been translated to the mouse vagus nerve model. Here we demonstrated that this microwire based approach was effective in obtaining chronic neural recordings and identifiable CAPs from the cervical vagus nerve in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vagus nerve recordings have been conducted under anesthesia for both acute (WOODBURY & WOODBURY 1991;Caravaca et al 2017;Dias Da Silva et al 2002;Krolczyk et al 2008) and chronic models (Caravaca et al 2017;Sauter et al 1983). Others have chronically recorded from the peripheral sciatic nerve in awake rat models (Michoud et al 2017;Srinivasan et al 2015;Gore et al 2015;Srinivasan et al 2016;Musick et al 2015;Vasudevan et al 2017) and from the vagus nerve in anesthetized rat models (Khodaparast et al 2014;Khodaparast et al 2016;Somann et al 2018), but these devices have not been translated to the mouse vagus nerve model. Here we demonstrated that this microwire based approach was effective in obtaining chronic neural recordings and identifiable CAPs from the cervical vagus nerve in mice.…”
Section: Discussionmentioning
confidence: 99%
“…) of the vagus nerve. Preclinical studies for chronic vagus nerve electrodes have been successfully conducted in large animal models (Zhang et al 2009;Ardell et al 2017;Hamann et al 2013;Metcalfe et al 2018;Valdés-Cruz et al 2002) and in rats (Somann et al 2017;McCallum et al 2017;Grimonprez et al 2015;Li et al 2004;Khodaparast et al 2016). Thus far, no studies for chronic mouse vagus nerve interfacing have been reported.…”
mentioning
confidence: 99%
“…However, conventional chronic nerve interfaces have geometries and mechanical properties that remain orders of magnitude divergent from those of the implant targets, increasing the risk of insult to host tissues, incidental damage to the nerve, and diminished efficacy due to poor compliance with the nerve (Grill et al, 2009;Minev et al, 2015;Salatino et al, 2017;Somann et al, 2017;Tyler and Durand, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that some approaches to PNS interfacing are associated with significant compromise of nerve health at both acute and chronic timepoints (Rydevik et al, 1981;Somann et al, 2017;Tyler and Durand, 2003), casting doubt on prior findings establishing the basic physiology of the periphery and the feasibility of bioelectronic therapeutic and restorative technologies. Thus, one of the principal design constraints was to develop an interface that minimized surgical complexity such that insult to the targeted nerve and the surrounding tissues would be minimal.…”
Section: Uncompromised Nerve Function Following Implantmentioning
confidence: 99%
See 1 more Smart Citation